스마트 관광 기술이 문화관광축제 경험과 재방문 의도 간의 관계에 미치는 영향 - 김현정(Hyun Jung Kim) (융합관광콘텐츠연구, 2021)
목적: 본 연구의 목적은 문화관광축제 경험이 재방문 의도에 미치는 영향을 살펴보고, 스마트 관광 기술이 문화관광축제 경험과 재방문 의도 간의 관계를 조절하는지를 검증하는 것이다. 방법: 본 연구는 위계적 회귀분석을 이용하여 스마트 관광 기술의 수준에 따라 문화관광축제 경험이 재방문 의도에 미치는 긍정적인 영향이 강화되는지를 분석하였다. 결과: 분석 결과는 다음과 같다. 첫째, 관광객의 문화관광축제 경험에 대한 호의적인 평가는 재방문 의도에 긍정적인 영향을 미쳤다. 둘째, 스마트 관광 기술의 속성 중에서 정보성, 상호작용, 개인화가 높을수록 문화관광축제 경험이 재방문 의도에 미치는 긍정적인 영향이 강화되었다. 결론: 본 연구는 문화관광축제 경험에 대한 호의적인 평가가 재방문 의도를 향상시키고, 스마트 관광 기술이 이러한 인과관계를 강화하는 것을 입증함으로써, 관광산업의 실무자들이 문화관광축제를 효과적으로 운영할 수 있도록 한다. Purpose: This study aims to examine the effect of cultural tourism festival experiences on revisit intention and to verify whether smart tourism technology moderates the relationship between cultural tourism festival experiences and revisit intention. Methods: This study used hierarchical regression analysis to analyze whether the positive impact of cultural tourism festival experiences on revisit intention is reinforced according to the level of smart tourism technology. Results: The analysis results are as follows. First, favorable evaluation of tourists’ experiences of cultural tourism festival had a positive effect on their intention to revisit. Second, among the attributes of smart tourism technology, the higher the informativeness, interactivity, and personalization, the stronger the positive effect of the cultural tourism festival experiences on revisit intention. Conclusion: This study found that favorable evaluation of the cultural tourism festival experiences improved the revisit intention, and smart tourism technology strengthened this causal relationship. Therefore, practitioners in the tourism industry can effectively manage the cultural tourism festival. KCI Citation Count: 6